Evaluation of the Antitumor Activity of Dacomitinib in Models of Human Bladder Cancer - Petros D. Grivas; Kathleen C. Day; Andreas Karatsinides; Alyssa Paul; Nazia Shakir; Iya Owainati; Monica Liebert; Lakshmi P. Kunju; Dafydd Thomas; Maha Hussain; Mark L. Day (Molecular Medicine, 2013)
Abstract Members of the human epidermal growth factor receptor (HER) family play a significant role in bladder cancer progression and may underlie the development of chemotherapy resistance. Dacomitinib is an irreversible tyrosine kinase inhibitor with structural specificity for the catalytic domains of epidermal growth factor receptor (EGFR), HER2 and HER4 that has exhibited vigorous efficacy against other solid tumors. We evaluated the antitumor activity of dacomitinib in human bladder cancer cell lines expressing varying levels of HER family receptors. These cell lines also were established as bladder cancer xenografts in nonobese diabetic/severe combined immunodeficiency (NOD/SCID) mice to assess dacomitinib activity in vivo. Significant cytotoxic and cytostatic effects were noted in cells expressing elevated levels of the dacomitinib target receptors with apoptosis and cell cycle arrest being the predominant mechanisms of antitumor activity Cells expressing lower levels of HER receptors were much less sensitive to dacomitinib. Interestingly, dacomitinib was more active than either trastuzumab or cetuximab in vitro, and exhibited increased growth inhibition of bladder tumor xenografts compared with lapatinib. Pharmacodynamic effects of dacomitinib included decreased E-cadherin (E-cad) expression, reduction of EGFR and extracellular signal-regulated kinase (ERK) phosphorylation and reduced mitotic count. Dacomitinib also inhibited tumor growth in a chemotherapy-resistant xenograft and, when combined with chemotherapy in a sensitive xenograft, exhibited superior antitumor effects compared with individual treatments. Evaluation in xenograft-bearing mice revealed that this combination was broadly feasible and well tolerated. In conclusion, dacomitinib exhibited pronounced activity both as a single agent and when combined with chemotherapy in human bladder cancer models. Further investigation of dacomitinib in the preclinical and clinical trial settings is being pursued.